2005
DOI: 10.1159/000086273
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Circulating Adiponectin in Women with Polycystic Ovary Syndrome

Abstract: Background and Aim: Adiponectin is regarded as a possible link between adiposity and insulin resistance. Ghrelin and leptin are considered as signals of energy status. We evaluated the relationships between these peptides, androgens and insulin sensitivity in women affected by polycystic ovary syndrome. Methods: Thirty-six women with PCOS were examined with euglycemic hyperinsulinemic clamp (to determine M/I, index of insulin sensitivity). Leptin, ghrelin, adiponectin, androgens, and SHBG were determined. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 101 publications
(58 reference statements)
4
10
2
Order By: Relevance
“…These results suggest a very high risk for the metabolic syndrome in obese PCOS patients and support that metabolic screening is of high relevance especially in this subgroup of patients. Our findings of significantly lower adiponectin levels in PCOS than in weightmatched controls as well as the close, inverse relation between adiponectin and BMI have previously been reported (8,10,11,23,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results suggest a very high risk for the metabolic syndrome in obese PCOS patients and support that metabolic screening is of high relevance especially in this subgroup of patients. Our findings of significantly lower adiponectin levels in PCOS than in weightmatched controls as well as the close, inverse relation between adiponectin and BMI have previously been reported (8,10,11,23,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 88%
“…These results may seem conflicting as previous studies have described significantly higher adiponectin levels in women than in men (34,35) and furthermore, that testosterone supplementation was followed by decreased adiponectin levels (34,36). However, our data are supported by two previous studies finding significant positive associations between adiponectin and testosterone levels in PCOS (11,32). Vribkova et al suggested that this association was caused by a more complex interrelation between testosterone, oestradiol and adiponectin in PCOS (32).…”
Section: Whr Adjustedsupporting
confidence: 91%
See 2 more Smart Citations
“…The production of adiponectin is decreased in obesity (8,9), and its plasma levels have been shown to correlate negatively with waist-to-hip ratio (WHR, 11) and body mass index (BMI,8). Decreased plasma levels of adiponectin have been observed in subjects with type 2 diabetes mellitus and coronary artery disease (12), and in women with PCOS (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%